Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/rheumatology/keg362
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland involvement in rheumatoid arthritis and its relationship to induced oxidative stress

Abstract: The effects of RA on salivary gland flow rates and antioxidant compositional parameters may be of great importance for the further elucidation of the role of free radicals in RA pathogenesis and for its general diagnosis and evaluation. The demonstrated correlation between the altered salivary parameters and the severity of the disease may indicate that evaluation of the salivary status of RA patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 23 publications
(34 reference statements)
2
31
0
Order By: Relevance
“…The currently reported increase in various salivary antioxidant parameters is of no surprise; in recent years, oxidative stress has become increasingly recognized as one of the major factors contributing to the chronic inflammatory process both in RA and in JIA patients (9,11,(29)(30)(31)(32)(33). Furthermore, increased MMP expression and activity was reportedly induced by the greater oxidative stress in general and also in rheumatoid synovial cells, as was shown in numerous studies; and vice versa, MMP expression and activity was decreased by antioxidants such as vitamin E or SOD (18,(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The currently reported increase in various salivary antioxidant parameters is of no surprise; in recent years, oxidative stress has become increasingly recognized as one of the major factors contributing to the chronic inflammatory process both in RA and in JIA patients (9,11,(29)(30)(31)(32)(33). Furthermore, increased MMP expression and activity was reportedly induced by the greater oxidative stress in general and also in rheumatoid synovial cells, as was shown in numerous studies; and vice versa, MMP expression and activity was decreased by antioxidants such as vitamin E or SOD (18,(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also was shown to induce various inflammatory mediators of rheumatoid arthritis, such as prostaglandins formed by Cox-2 in the synovium (44). Such proinflammatory cytokines have been shown to induce MMPs and, therefore, it is not surprising that anti-TNF therapies have been found to reduce serum MMP levels in patients with RA (11)(12)(13)(14). Indeed, Mentzel et al, (45) who studied a rat model for antigen-induced arthritis, reported that TNF-α increased total MMP activity, levels of IL-6 and oxidant nitric oxide (NO) in the supernatants of synoviocytes, and induced the expression of MMP9 (as did IL-1β).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanism of the impairment of salivary gland function has been studied, but a detailed understanding of it has not yet been achieved. However, it has been supposed that reactive oxygen species (ROS) are involved in the impairment of salivary gland function due to aging, inflammation, drugs, and ionizing irradiation [1][2][3][4]. Not only extracellular but also intracellular ROS regulate cellular biological activities by activation and also suppression of proteins as well as by modification of DNA [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these ROS, there are a variety of oxidized reactive lipids, which are associated with damage of blood vessel walls, perfusion-induced damage of the brain, and apoptotic degeneration of liver and kidney cells [11][12][13][14]. Of the ROS, O 2 -is crucial in this damage because O 2 -leads to generation of OH .…”
Section: Introductionmentioning
confidence: 99%